Convection of internal-heated two-layer fluids with deformable interface under swinging motion conditions. (25th February 2020) - Luo, Simin; Zhang, Yapei; Zhang, Dalin; Su, G.H.; Qiu, Suizheng
Highlights: Experiments of two-layer fluids convection under swinging conditions were conducted. Temperature field and heat transfer can be greatly changed by swinging motions. Phenomena of the interface deformation under swinging motions were discussed. Abstract: Convection inside a layered system has been a significant research focus. Different from the known research under static condition, this study experimentally investigated the convection phenomena of internal-heated two-layer fluids systems under swinging motion conditions. The effects of swinging motions on the major convection phenomena related parameters were studied, including the system temperature fields and heat transfer capacities, together with the sensitivity analyses of maximum swinging angle and swinging period. Additionally, phenomenological research was carried out on the pattern of interface deformation between the two layers under swinging motions. From the experiment, it's found that swinging motions can weaken the thermal stratification occurring in the internal-heated two-layer system under static condition, and intensify heat transfer from the system to the outer cooling boundary. A wave shape of interface is observed with the declining swinging period, and unstable interface deformations can be seen during swinging motions with a large maximum swinging angle but a small swinging period, with mixing or penetration observed between the two liquids. Moreover, a thicker layer of upper fluid refrains interface deformation and thus helps to stabilize two-layer system during swinging motions. This study can be helpful for the nuclear safety management strategy related to the analysis of stratified corium pools in the marine environment.